SOCIAL CAPITAL AND MUTUAL VERSUS PUBLIC BENEFIT: THE CASE OF RENEWABLE ENERGY COOPERATIVES. (25th April 2017) - BAUWENS, Thomas; DEFOURNY, Jacques
ABSTRACT: One potential major role of social economy organizations in sustainability transitions is the creation and mobilization of social capital. Yet, the social economy gathers very distinct organizational models which may be associated with different types and levels of social capital. Accordingly, the objective of this article is to explore whether, and if so how, the type and level of social capital differ between mutual benefit organizations – which essentially seek to meet their members' needs – and public benefit organizations – which seek to enhance the well‐being of a broader community or the society as a whole. The study draws on an econometric analysis of different forms of social capital in two renewable energy cooperatives which are located in Flanders but have clearly divergent orientations toward mutual versus public benefit. The results show that, as compared with an orientation toward public benefit, an orientation toward mutual benefit is associated with lower social identification with the cooperative and weaker ties between members. Our study explores the underlying explanatory mechanisms behind these relationships. Its findings contribute to understanding the potential roles played by cooperatives in sustainability transitions.